Success rate of intrauterine insemination in patients with unknown infertility - Jašović Vladimir; Jašović-Siveska Emilija (Vojnosanitetski Pregled, 2012)
Background/Aim. Unknown cause of infertility exists in 10%-26% of couples with infertility problems. Treatment of these couples depends on the possibility of correcting the unidentified defect over time. Intrauterine insemination (IUI) and ovaluation stimulation are methods of choice in treatment of unexplained fertility, but if a woman is older than 37 years, in vitro fertilization (IVF) could be directly recommended. The aim of this research was to compare the success rate of pregnancies with IUI between the patients with unexplained infertility and the patients with mild form endometriosis. Methods. The study included on 50 patients diagnosed with mild form endometriosis (group A) and 50 patients with unknown cause infertility (group B). Using the same therapeutical protocol, human menopausal gonadothropin (hMG) stimulation and horionic gonadropin (hCG) induction were applied, as well as IUI. Results. The percentage of achieved ovulation was higher in the group B (p < 0.05). During the 3 simulated sequential periods 102 IUI were performed in the group A and 97 IUI in the group B. In the group A there were 6 single and 1 twin pregnancies sucesfully conceived (14%), while in group B there were 9 (18%) single pregnancies. Conclusion. The use of a combination of controled ovarian hyperstimulation and IUI is an effective, cheap and safe method for treating infertility couples, especially couples with unknown cause infertility. Mild form endometriosis, as etiological infertility factor, has a negative impact on IUI success rate.